2009
DOI: 10.1093/aob/mcn266
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of LEAFY COTYLEDON1-LIKE gene and localized auxin accumulation mark embryogenic competence in epiphyllous plants of Helianthus annuus × H. tuberosus

Abstract: In EP leaves, Ha-L1L activity marks the putative founder cells of ectopic embryos. Although the ectopic expression of Ha-L1L seems to be not directly mediated by auxin levels per se, it was demonstrated that localized Ha-L1L expression and IAA accumulation in leaf epidermis domains represent early events of somatic embryogenesis displayed by the epiphyllous EMB-2 clone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 77 publications
(101 reference statements)
0
24
0
2
Order By: Relevance
“…Expression of LEC2 (Ledwoń and Gaj, 2009) together with LEC1 and FUS3 (Ledwoń and Gaj, 2011) was observed in callus tissue developing on auxin-rich medium. As in sunflower (Fambrini et al, 2006;Chiappetta et al, 2009), LEC1 expression was not observed in cultures induced to regenerate shootlike structures, but the gene was highly active in embryogenic cells.…”
Section: Discussionmentioning
confidence: 86%
“…Expression of LEC2 (Ledwoń and Gaj, 2009) together with LEC1 and FUS3 (Ledwoń and Gaj, 2011) was observed in callus tissue developing on auxin-rich medium. As in sunflower (Fambrini et al, 2006;Chiappetta et al, 2009), LEC1 expression was not observed in cultures induced to regenerate shootlike structures, but the gene was highly active in embryogenic cells.…”
Section: Discussionmentioning
confidence: 86%
“…DIG-labeled RNA sense and anti-sense probes were obtained as described in Bruno et al (2009a). Immunological detection was as reported by Chiappetta et al (2009). Transcript accumulation was visualized as a violet/brown staining.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen µl were electrophoresed in a 1% agarose gel; each signal was determined using quantitative optical densitometry (OD ± SD) based on the pixel intensity/ area of each PCR product as described in Chiappetta et al (2009). Three replicate analyses were performed and density differences were evaluated using Tukey's test.…”
Section: Methodsmentioning
confidence: 99%
“…The altered cell division in EMS mutant as well as the level of TOZ and TTN6 gene transcripts at different stage of seed development suggested that TOZ and TTN6 genes could also play a direct role in Phaseolus in regulating cell division. Interestingly, the transcript levels of several genes required for controlling embryo and seed development, such as PEI (Li and Thomas 1998), and for coordinating the morphogenesis phases, such as L1L (Chiappetta et al 2009), were altered in EMS mutant relative to the wild-type (Fig. 5).…”
Section: Plant Cell Tiss Organ Cultmentioning
confidence: 99%